2022
DOI: 10.1021/acsanm.2c04674
|View full text |Cite
|
Sign up to set email alerts
|

CuCo2O4/NiCo-Metal–Organic Framework Nanoflake Arrays for High-Performance Supercapacitors

Abstract: Developing hybrid metal−organic frameworks (MOFs) with ordered structure is significant to obtain promising electrode materials for supercapacitors. Herein, the special electrodes of CuCo 2 O 4 /NiCo-MOF nanoflake vertical arrays are constructed on Ni foam by using the CuCo 2 O 4 nanorods as a selfsacrifice template. Because of the multidirectional interconnected channels of spinel CuCo 2 O 4 , great electrochemical activity of NiCo-MOF, well-arranged morphology, and synergy effect at the interface, the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Figure 4e exhibits the fine spectrum of Co 2p in CCO@N 0.5 C 0.5 OH/NF; the peaks at 798.08, 796.58, 782.18, and 780.78 eV correspond to Co 2+ 2p 1/2 , Co 3+ 2p 1/2 , Co 2+ 2p 3/2 , and Co 3+ 2p 3/2 , while the two satellite peaks are located at 802.78 and 785.98 eV, respectively. [ 33 ] From the spectra, it can be observed that the content of Co 3+ ions is higher than that of Co 2+ ions, which can be attributed to the presence of Cu atoms that occupy some of the tetrahedral sites of Co 2+ ions, resulting in a relatively higher content of Co 3+ ions in the octahedral sites compared with Co 2+ ions. [ 67 ] Additionally, the binding energy of Co 2p is increased by 0.7 eV after the modification of CCO/NF by anchoring N 0.5 C 0.5 OH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 4e exhibits the fine spectrum of Co 2p in CCO@N 0.5 C 0.5 OH/NF; the peaks at 798.08, 796.58, 782.18, and 780.78 eV correspond to Co 2+ 2p 1/2 , Co 3+ 2p 1/2 , Co 2+ 2p 3/2 , and Co 3+ 2p 3/2 , while the two satellite peaks are located at 802.78 and 785.98 eV, respectively. [ 33 ] From the spectra, it can be observed that the content of Co 3+ ions is higher than that of Co 2+ ions, which can be attributed to the presence of Cu atoms that occupy some of the tetrahedral sites of Co 2+ ions, resulting in a relatively higher content of Co 3+ ions in the octahedral sites compared with Co 2+ ions. [ 67 ] Additionally, the binding energy of Co 2p is increased by 0.7 eV after the modification of CCO/NF by anchoring N 0.5 C 0.5 OH.…”
Section: Resultsmentioning
confidence: 99%
“…The superior electrochemical performance of the CCO@N 0.5 C 0.5 OH/NF electrode may result from the following factors: 1) the porous mesh structure of the NF effectively prevents the aggregation of nanomaterials, reduces the “dead volume” in the electrode, and enhances the utilization rate of the active material. [ 33 ] Additionally, the excellent electrical conductivity of NF promotes efficient electron transfer between the nanomaterials and the current collector, facilitating the redox reaction of the electrode material. [ 22 ] Furthermore, the stable framework structure of NF mitigates mechanical deformation during the charge–discharge process, contributing to the improved cycling stability of the electrode material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] However, Li resources are limited, and the actual energy density of Li-ion batteries is approaching the technological limit, making the development prospects of traditional Li-ion batteries indistinct. [6][7][8][9][10] Mg is considered one of the options for the generation of energy storage technologies because of its abundance, low price, dendrite-free nature, and higher theoretical volumespecific capacity (3833 mA h cm −3 ) than that of Li (2046 mA h cm −3 ). [11][12][13] However, Mg 2+ has two positive charges, which creates an intense coulombic force between Mg 2+ and the cathode material, resulting in the slow diffusion of Mg 2+ in the cathode material and easy polarization.…”
Section: Introductionmentioning
confidence: 99%
“…1–5 However, Li resources are limited, and the actual energy density of Li-ion batteries is approaching the technological limit, making the development prospects of traditional Li-ion batteries indistinct. 6–10…”
Section: Introductionmentioning
confidence: 99%